Numerical simulation study on coal seam response characteristics of shallow three-electrode laterolog - Qi, Xinghua; Wang, Shimao; Wei, Yuxuan; Wang, Zhuwen (Frontiers in Earth Science, 2025)
Shallow three-electrode laterolog is widely used in the field of coal field logging because of its strong economy. Coal seams in Xinjiang region have the characteristics of large thickness variation, high dip angle, easy diameter enlargement and fracture development, but the law of these characteristics in the three-electrode laterolog curve is not clear. In this paper, through the finite element simulation software COMSOL Multiphysics, 2D and 3D models are constructed based on shallow three-electrode laterolog, and the characteristics of using shallow three-electrode laterolog in coal field logging are studied. The results show that the electrode system coefficient of shallow three-electrode laterolog instrument should be 0.94 times of the theoretical electrode system coefficient. The discrimination ability of shallow three-electrode laterolog to coal seams is about 0.3 m. There is a power function relationship between the determination coefficient of coal seam boundary and the ratio of coal seam-surrounding rock resistivity ratio. An increase in the dip angle of the coal seam leads to an increase in the apparent thickness of the coal seam following a quadratic function relationship, while an increase in the wellbore radius results in a quadratic function decrease in the apparent resistivity of the coal seam. An increase in both the width and length of the fractures leads to a decrease in apparent resistivity following a power function relationship. The research results provide a more accurate reference standard for the analysis and evaluation of coal seams using shallow three-electrode laterolog.